EVALUATION OF INCIDENCE OF ADYNAMIC BONE DISEASE IN PATIENTS WITH END STAGE RENAL DISEASE - HAROON, M; ANJUM, N; TARIQ, S (Biological and Clinical Sciences Research Journal, 2022)
To assess frequency of adynamic bone disease in subjects with ESRD a Prospective study was carried out at Department of Medicine, Services Hospital Lahore from 6 months from January 2022 to July 2022. Demographic data of the subjects including gender, age, BMI, smoking history, socioeconomic status and duration of dialysis and end stage renal disease was recorded. Blood samples of all patients were drawn and sent to the laboratory for evaluation of phosphate, calcium, alkaline phosphatase and iPTH levels. Findings of the laboratory tests were analyzed and adynamic bone diseases were diagnosed according to operational definition. The study was conducted on 135 patients whose mean age was 50.31±12.56 years. According to this study, adynamic bone disease was found in 34(25.19%) patients. Association between adynamic bone disease and duration of ESRD, duration of dialysis was statistically insignificant (p>0.05). Adynamic bone disease was reported in 25.2% of patients having ESRD.